Actuator attack detection and power balance for cyber physical power systems. Issue 6 (8th December 2022) - Li, Jian; Li, Hongliang; Wang, Handong; Su, Qingyu
Abstract: In this paper, the problem of attack detection for actuator attacks and power balance on cyber physical power systems (CPPSs) is investigated. An economic optimization strategy based on observer data is proposed to enable optimal power balance of the attacked system. System states and cyber attacks are estimated by a sliding mode observer satisfying the H ∞ $H_{∞ }$ performance index. Then, the system power is redistributed according to the optimal economic dispatch. Finally, several simulation cases are presented to illustrate the effectiveness of attack detection and economic optimization strategy. Abstract : The problem of attack detection and economic optimization strategy for actuator attacks on cyber physical power systems (CPPSs) is investigated. An power balance strategy based on observer data is proposed to enable optimal power adjustment of the attacked system.